Educational needs and type 1 diabetes mellitus: The voices of adolescents, parents and caregivers. (March 2022) - Mayen, Sandrine; Lagouanelle-Simeoni, Marie-Claude; Cote, José; Fonte, David; Reynaud, Rachel; Gentile, Stéphanie; Colson, Sébastien
Objectives: The aim of this study was to describe the needs of adolescents with type 1 diabetes mellitus for acquiring self-care and psychosocial skills for the progressive self-management of the disease, as a prelude to the development of an educational programme. The parents and health care professionals who supported young people were also asked to provide their insight into adolescents' needs. Methods, design and setting: Qualitative focus group design with a thematic analysis informed by social-cognitive theory. Results: Findings highlight gaps and divergence in the perceived needs of adolescents engaged with in existing structured educational programmes. Suggestions for change to future programmes were identified, including the implementation of educational follow-ups outside of hospital settings and an educational programme open to family and friends to foster support from the adolescents' social circle. The use of digital media is proposed as an on-demand (rather than planned) educational method. Conclusion: This study provides information relevant to the development of new educational programmes for adolescents with type 1 diabetes in the south of France. Future programmes should be structured so as to promote active participation by adolescents from the start of the programme through to its evaluation.